Decentralized congestion mitigation in HV distribution grids with large penetration of renewable generation. (October 2015) - Berizzi, Alberto; Bovo, Cristian; Ilea, Valentin; Merlo, Marco; Miotti, Alessandro; Zanellini, Fabio
Highlights: An on-line decentralized congestion mitigation (CM) algorithm is proposed. CM mitigates congestions due to renewables in the high voltage distribution grids. CM can use the low performance communication system of this part of the network. CM is implementable at substation level, in the available, low performance, hardware. Tests on a real-life benchmark system show the performances of the algorithm. Abstract: The integration of large amounts of Renewable Energy Sources (RES) is a great challenge for the operation of current power systems. In the Italian HV distribution system the main threat to security is caused by congestions that are likely to result in significant RES curtailment. This paper proposes an automatic procedure to be implemented in the Substations Automation Systems (SASs) to locally define control actions to mitigate congestions in such a way that RES curtailment is minimized. The algorithm assumes a reduced set of available data, simple computations and is especially designed to operate on-line as a decentralized automation function. Hence, the methodology intentionally avoids burdensome computations: it neither requires the knowledge of the complete network structure nor imposes any particularly strict requirement on the communication system. The effectiveness of the proposed methodology is shown with reference to a real model of a section of the Italian 150 kV grid.